Hybrid Energy Storage (Springer Nature, 2025)
This is an open access book that addresses the need for hybridization in energy storage, offering a fresh perspective on integrating diverse storage solutions to support a successful energy transition. It fills a significant gap in the literature by presenting a comprehensive collection of case studies and real-world examples, while tackling challenges across multiple sectors, including industrial operations, grid, off-grid systems, transportation, and smart building applications. Authored by a multidisciplinary team of leading experts, the book explores technology-neutral requirements for different applications and examines the key drivers behind system installations. It proposes innovative hybrid energy storage solutions grounded in detailed techno-economic and sustainability analyses. Furthermore, by identifying untapped opportunities for electrification and system integration, the book positions itself as a valuable resource for advancing the European Union’s goals of decarbonization and energy security. By addressing critical hybridization needs, offering a thorough literature review, and presenting application-oriented solutions, it empowers researchers, industry professionals, and policymakers to make informed decisions, while also educating the next generation of scientists and engineers in innovative energy storage approaches.